2020
DOI: 10.1080/15476286.2020.1712895
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer RNAs in cancer: regulation, mechanisms and therapeutic potential

Abstract: Enhancers are distal genomic elements critical for gene regulation and cell identify control during development and diseases. Many human cancers were found to associate with enhancer malfunction, due to genetic and epigenetic alterations, which in some cases directly drive tumour growth. Conventionally, enhancers are known to provide DNA binding motifs to recruit transcription factors (TFs) and to control target genes. However, recent progress found that most, if not all, active enhancers pervasively transcrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 123 publications
(257 reference statements)
2
82
0
Order By: Relevance
“…eRNAs have attracted particular interest due to their potential roles in mediating enhancer functions and gene transcription associated with cancers [ 22 ]. The aim of the present study is to explore the eRNAs as prognostic related biomarker in OV.…”
Section: Discussionmentioning
confidence: 99%
“…eRNAs have attracted particular interest due to their potential roles in mediating enhancer functions and gene transcription associated with cancers [ 22 ]. The aim of the present study is to explore the eRNAs as prognostic related biomarker in OV.…”
Section: Discussionmentioning
confidence: 99%
“…As distal genomic elements, enhancers can provide DNA binding motifs to recruit transcription factors (TFs) and regulate target genes 12 . The enhancer malfunction may induce genetic and epigenetic alterations, which in turn activate oncogene expression and drive tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancer RNAs (eRNAs), a type of noncoding RNAs transcribed from the enhancer, help to explore the mechanisms of enhancers and also participate in cancer development 11 . Its expression is also various in different tumor types and individual patients, thus may serve as potential diagnosis markers or therapeutic targets 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on this physiological process, a series of works [ 18 , 19 ] confirmed that the promoter-proximal pausing of Pol II is a crucial postrecruitment and rate-limiting step for gene regulation. In addition, eRNA transcription serves as a robust indicator of enhancer activation, and have potential roles in mediating enhancer functions and gene transcription [ 20 ā€“ 22 ], which can be applied to understanding the transcriptional regulation of disease, like tumorigenesis [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%